Burnout in gastroenterology registrars: a feasibility study conducted in the East of England using a 31-item questionnaire. Issue 1 (14th July 2020) - Ong, John; Swift, Carla; Ong, Sharon; Lim, Wan Yen; Al-Naeeb, Yasseen; Shankar, Arun
Abstract : Objective: The scale of burnout in UK gastroenterology trainees and the feasibility to determine its prevalence using the validated Maslach Burnout Inventory-Human Services Survey (MBI-HSS) tool are unknown. The primary objective of this region-wide pilot study was to evaluate the response rate to a 31-item questionnaire. The secondary objectives were to estimate the prevalence of burnout in gastroenterology trainees within the East of England deanery (EoE) and identify common stressors that trainees experience. Design: This was a cross-sectional study involving gastroenterology trainees from 16 hospitals across the EoE using a 31-item questionnaire. The questionnaire consisted of the 22-item MBI-HSS and nine additional free-text questions. All gastroenterology trainees in the EoE were invited to complete the anonymised survey online. Data were analysed quantitatively and qualitatively. Results: The response rate for the survey was acceptable: 44.0% (40/91). 57.5% (23/40) of gastroenterology trainees reported emotional exhaustion. 23.5% (8/34) had depersonalisation and 63.9% (23/36) experienced low professional accomplishment. Burnout prevalence was 35.3% (12/34). 48.4% (15/31) of gastroenterology trainees were aware of professional support services within EoE. Stressors related to service requirements (eg, workload, staffing levels) and professional relationships with colleagues and patients were commonly reported: 65.6% and 25.0%, respectively. Conclusions: It is feasible to use a 31-item questionnaire in a national cohort of UK gastroenterology trainees for future burnout studies. Burnout in EoE gastroenterology trainees was high and this may reflect a national prevalence within the specialty. More extensive studies, greater awareness of burnout and improved access to professional support services are required.